Potensi Antidiabetes Fraksi Etil Asetat dari Ekstrak Etanol Batang Ubi Yakon (Smallanthus sonchifolius) Secara in Vivo - Efendi, Alvira; Haryoto, Haryoto (Journal of Pharmaceutical and Sciences, 2025)
Diabetes mellitus is one of the global health problems that requires alternative therapies based on natural products. The stem of yacon (Smallanthus sonchifolius) is known to contain various secondary metabolites with potential antidiabetic effects. This study aimed to identify the secondary metabolites in the ethyl acetate fraction of yacon stem, evaluate its antidiabetic activity in alloxan-induced male Wistar rats, and determine the lowest effective dose. Phytochemical screening revealed the presence of flavonoids, terpenoids, steroids, tannins, and alkaloids. The in vivo test was conducted by administering the ethyl acetate fraction at doses of 25, 50, and 100 mg/kgBW to Wistar rats, with negative and positive control groups using metformin. The results showed that all treatment doses significantly reduced blood glucose levels compared to the negative control, with hypoglycemic effects observed from day 7 and becoming more pronounced until day 21. The 25 mg/kgBW dose was the lowest dose that produced effects comparable to metformin and thus can be considered the lowest effective dose. These findings indicate that yacon stem has the potential to be developed as a natural agent for antidiabetic therapy.